2018
DOI: 10.4314/njt.v36i4.40
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of rainfall IDF equation types for predicting rainfall intensity in southern Nigeria

Abstract: This paper compared the differences and similarities in the rainfall intensities predicted by four standard IDF equations for return periods between 5 and 40 years and for storm durations between 15 and 30 minutes. The empirical models employed for comparison on the development of standard IDF equations using historic data for Benin, Calabar, Port Harcourt, Onitsha and Warri meteorological stations, all in Southern Nigeria were available in literature. The strength and weakness of the different models were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The establishment of such relationship was done as early as 1932 [1]. The knowledge of frequency of extreme events like floods, droughts, rainstorm and high winds assisted in planning and design for these extreme events [2]. The planning and designing of various water resource projects requires the use of rainfall intensity-duration-frequency (IDF) relationship [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of such relationship was done as early as 1932 [1]. The knowledge of frequency of extreme events like floods, droughts, rainstorm and high winds assisted in planning and design for these extreme events [2]. The planning and designing of various water resource projects requires the use of rainfall intensity-duration-frequency (IDF) relationship [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Regression and correlation analyses were used with most of the results presented as equations and in graphical form. Further studies by some scholars [17][18][19][20] examined the predictive ability of different types of IDF models for Abakaliki and selected cities in Southern Nigeria, respectively. They concluded that simple two parameter quotient IDF type model predicted higher intensity at duration equal or less than 30 minutes and also predicted lowest relative error.…”
Section: Rainfallmentioning
confidence: 99%
“…Studies conducted in Nigeria on IDF development are all site specific and are also based on the stationary concept [20,21,35,36,37]. Most of the studies applied short precipitation records varying between 10 to 13 years except for those of [37] which were between 17 -35 years term. The various studies focused on derivation of deterministic IDF models where the variables are defined by the parameters of the calibrated equations.…”
Section: Parametric Idf Modelingmentioning
confidence: 99%